Developing Motion Graphics “Successful English Presentation” for Tertiary Vocational Students - Arta Uly Siahaan (Universitas Muhammadiyah Jember, 2022)
Communication skills in both oral and written English are significant assets for students to enter the industrial world. Preliminary studies revealed that tertiary vocational students (subjects are 66 Polibatam students) find it challenging to speak in English, especially when making presentations in English (77, 3%), which is a reasonably frequent activity in the industry. Therefore, developing alternative learning media is essential for students. It can be a source of learning independently, as well as an alternative teaching media for lecturers. This research aims to create and analyze motion graphics videos to support speaking practice aimed at vocational higher students. The content is about introducing English presentation and making a successful presentation. The method used in this study is R and D that started from identification or need analysis, design, development of the product, evaluation and final product. The field testing carried out is the alpha testing and beta testing. The developers themselves will conduct alpha testing which involved three media reviewers. Meanwhile, for beta testing, the motion graphic was tested to the English lecturer as the content reviewers and the students as the target to use this product. The result shows that the product was excellent to be used as alternative media for speaking practice even to be used by the lecturer as the media for asynchronous class.